2018
DOI: 10.1136/bmjopen-2018-023114
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and geographic patterns of stab injuries in young people: a retrospective cohort study from a UK major trauma centre

Abstract: ObjectivesTo describe the epidemiology of assaults resulting in stab injuries among young people. We hypothesised that there are specific patterns and risk factors for injury in different age groups.DesignEleven-year retrospective cohort study.SettingUrban major trauma centre in the UK.Participants1824 patients under the age of 25 years presenting to hospital after a stab injury resulting from assault.OutcomesIncident timings and locations were obtained from ambulance service records and triangulated with pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 18 publications
7
39
0
Order By: Relevance
“…Children 10 to 14 years of age were most likely to be assaulted at school and by a friend or acquaintance. This finding is consistent with other studies [ 6 , 11 ] which found that older children and adolescents tended to experience more violent injury further away from home.…”
Section: Discussionsupporting
confidence: 93%
“…Children 10 to 14 years of age were most likely to be assaulted at school and by a friend or acquaintance. This finding is consistent with other studies [ 6 , 11 ] which found that older children and adolescents tended to experience more violent injury further away from home.…”
Section: Discussionsupporting
confidence: 93%
“…Epidemiological, health services studies are increasingly using geospatial methods [ 12 14 ] to better understand and target both injury prevention and post-injury care [ 15 ]. Triage optimisation using geospatial data and scenario modelling has demonstrated significantly reduced time to SCIU admission in a Canadian study [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological, health services studies are increasingly using geospatial methods (11)(12)(13) to better understand and target both injury prevention and post-injury care (14). Triage optimisation using geospatial data and scenario modelling has demonstrated signi cantly reduced time to SCIU admission in a Canadian study (15).…”
Section: Introductionmentioning
confidence: 99%